Optimizing Internal Audit Roles for Fraud Prevention in Higher Education: Optimalisasi Peran Audit Internal dalam Pencegahan Penipuan di Perguruan Tinggi - Anggraini, Amelia Putri; Hanun, Nur Ravita (Indonesian Journal of Education Methods Development, 2025)
Background: Fraud in higher education remains a persistent challenge due to complex organizational structures and weak oversight mechanisms. Specific Background: Previous studies mostly examined technical aspects of internal audit without exploring its practical effectiveness across diverse campus contexts. Gap: Limited qualitative investigations addressing how internal audit functions operate in different institutional settings. Aim: This study explores the effectiveness of internal audit roles in preventing fraud in three higher education institutions. Methods: A qualitative approach was applied using semi-structured interviews, observations, and triangulation supported by secondary literature. Results: Internal audit performance in the three institutions remains suboptimal due to limited management support, inconsistent follow-up of audit recommendations, and oversight structures that emphasize administrative review rather than investigative depth. Novelty: This study provides a multi-institutional qualitative perspective showing how variations in audit structures produce different levels of fraud-prevention readiness. Implications: The findings highlight the need for strengthened governance systems, clearer authority for internal audit units, and systematic follow-up mechanisms to enhance institutional integrity. Highlights:• Internal audit effectiveness varies across institutions• Fraud prevention requires managerial commitment• Oversight structures shape audit performance Keyword: Internal Audit, Fraud Prevention, Higher Education, Internal Control, Qualitative Study